Design an Electrical Power Practical Module in the Introductory Electrical Energy Course - Manullang, Nursarinah; Fathiah, Fathiah; Ikhsan, Muhammad (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
The introductory electrical energy course is one of the courses that applies learning using practical methods. In the introductory electrical energy course, there is material about electrical power. Based on observations, it is known that students need more learning media in the form of modules in the electrical power practicum, which causes a lack of interest and low understanding of student learning. Based on these problems, a learning medium in the form of a practicum module was developed to complement practicum learning and is expected to increase students' interest in and understanding of learning. The electrical power practicum module was developed using research and development methods. The researcher's research instrument was a media expert and material expert validation sheet to test the feasibility of the practicum module to be applied in the Electrical Power Practicum. The validation results of media and material experts prove that the electrical power practicum module is very feasible regarding media and material. Based on the percentage of scores obtained from media experts, namely 81.66%, material experts obtained a score of 88.57%, which is included in the very suitable category to be applied in the Basic Electrical Energy course.